Harmonization of Rehabilitation Service Standards for Drug Abuse’s Addicts and Victims according to the Regulations - Refi Hendra (Faculty of Law, Universitas Lampung, 2021)
Narcotics addicts and victims of narcotics abuse must undergo medical and social rehabilitation, according to Article 54 of Indonesia's Narcotics Law. The government then issued a rehabilitation policy for them under the authority of three state institutions, namely the Ministry of Health, the Ministry of Social Affairs, and the National Narcotics Agency. This causes overlapping and tug-of-war among stakeholders when it comes to developing policies and implementing rehabilitation services for addicts and victims of narcotics abuse, resulting in no method that becomes a guideline for rehabilitation implementation, on the report of an Ombudsman study. The aim here is to investigate how the laws of Rehabilitation Service Standards for Addicts and Victims of Drug Abuse are harmonized. The approach used is normative juridical. According to the study's findings, the regulations are hierarchically aligned, but the implementation of each rehabilitation program has a Service Standard. There is a vertical disparity in the definitions of medical and social rehabilitation and service providers and service recipients. Horizontally, there are differences in the determination of the implementing agency, service standards such as service programs, human resources, infrastructure, and activity funding sources. As a result, medical and social rehabilitation implementation is separated, resulting in a lack of comprehensive services for service recipients.